2012
DOI: 10.4254/wjh.v4.i4.139
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cellular genes showing differential expression associated with hepatitis B virus infection

Abstract: The signature of cellular gene expression should provide new information regarding the pathophysiological mechanisms of persistent hepatitis and hepatocarcinogenesis that are associated with HBV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In order to determine whether the HBx is really responsible for the differential expression of genes in HepG2 and Hep3B cells, we examined the reported alteration of gene expression in HBx knockdown studies. Surprisingly, we found that none of the genes listed in Table 1 has been reported to be either up-or down-regulated in the human cells (Xie et al 2011) or in mouse model (Fukuhara et al 2012) when HBx is knocked down. This finding seems to suggest that the differential expression of genes between HepG2 and Hep3B is not simply dependent on HBx.…”
Section: Underlying Mechanisms Responsible For the Differences Betweementioning
confidence: 66%
“…In order to determine whether the HBx is really responsible for the differential expression of genes in HepG2 and Hep3B cells, we examined the reported alteration of gene expression in HBx knockdown studies. Surprisingly, we found that none of the genes listed in Table 1 has been reported to be either up-or down-regulated in the human cells (Xie et al 2011) or in mouse model (Fukuhara et al 2012) when HBx is knocked down. This finding seems to suggest that the differential expression of genes between HepG2 and Hep3B is not simply dependent on HBx.…”
Section: Underlying Mechanisms Responsible For the Differences Betweementioning
confidence: 66%